Advances in Manufacturing (Lecture Notes in Mechanical Engineering,, 2018)
This book covers a variety of topics in material, mechanical, and management engineering, especially in the area of machine design, product assembly, measurement systems, process planning and quality control. It describes cutting-edge methods and applications, together with exemplary case studies. The content is based on papers presented at the 5th International Scientific-Technical Conference (MANUFACTURING 2017) held in Poznan, Poland on 24-26 October 2017. The book brings together engineering and economic topics, is intended as an extensive, timely and practice-oriented reference guide for researchers and practitioners, and is expected to foster better communication and closer cooperation between universities and their business and industry partners. .